1998
DOI: 10.1046/j.1365-3040.1998.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of plant water use by rhizosphere and xylem conductance: results from a model

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
718
1
11

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 690 publications
(757 citation statements)
references
References 43 publications
27
718
1
11
Order By: Relevance
“…The convergence on a 'risky' hydraulic strategy exhibited by many species can be understood as the result of a trade-off that balances growth with protection against risk of mortality in a given environment 17,21,25 . Thus, a low safety margin to Y 50 also indicates that stomatal regulation takes full advantage of the range of xylem pressures that are within the tolerance of the hydraulic system of that species.…”
Section: Letter Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The convergence on a 'risky' hydraulic strategy exhibited by many species can be understood as the result of a trade-off that balances growth with protection against risk of mortality in a given environment 17,21,25 . Thus, a low safety margin to Y 50 also indicates that stomatal regulation takes full advantage of the range of xylem pressures that are within the tolerance of the hydraulic system of that species.…”
Section: Letter Researchmentioning
confidence: 99%
“…In drying soil, stomata initially regulate water loss from the leaves to maintain xylem pressure (Y x ; measured as water potential below 0) within a range that will protect the xylem from extensive embolism 17,21 . As drought continues, stomatal closure slows but does not halt the decline of xylem pressure and hydraulic capacity.…”
mentioning
confidence: 99%
“…This requires adjustment of the plant's conducting system to maximize water uptake and to reduce water deficits (Sperry et al 1998(Sperry et al , 2002Maseda and FernĂĄndez 2006). Trees adapt to changes in water availability either with long-term plastic responses in the size of the absorbing root system and in the evaporating leaf surfaces or by modifications in the hydraulic system and adjustment of the cavitation risk along the flow path (Sperry et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This is reflected in the tendency of models to overestimate stomatal conductance in the afternoon (Martin et al 1997), and the need to use timeof-day as a variable to account for the overestimation (Körner 1993). As a result, the assumption of small and constant root-soil resistance is only partially correct, even under conditions of low transpiration rates, or where plants with high root-to-leaf surface area ratios are monitored while absorbing water from moist, fine soils (Carbon et al 1980;Sperry et al 1998). However, under flooded conditions, the assumption of invariable resistance to water uptake from the soil is satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies have suggested that the absence of stomatal regulation would cause excessive xylem cavitation and failure of water transport (Tyree and Sperry 1988;Sperry et al 1993;Tyree et al 1993;Saliendra et al 1995;Cochard et al 1996;Lu et al 1996). This "hydraulic constraint" may be particularly important for species adapted to constant and high Κ S (Sperry et al 1998), such as T. distichum.…”
Section: Introductionmentioning
confidence: 99%